2014
DOI: 10.3109/13880209.2014.895389
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect ofAzadirachta indicaon advanced glycation end-product in streptozotocin-diabetic rat

Abstract: We found that A. indica is an inhibitor AGE formation, and oxidative stress with a renoprotective effect, which are considered to play important roles in diabetic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…This finding is supported by Shailey et al and Gutierrez et al, who reported that A. indica leaf extract showed significantly lower HbA1c levels in experimentally induced diabetic rats compared to the control group. 18,35 In addition to its anti-hyperglycemic effect, NEEM significantly improved endothelial function in T2DM subjects, compared to the placebo group. No such findings were available in the literature.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This finding is supported by Shailey et al and Gutierrez et al, who reported that A. indica leaf extract showed significantly lower HbA1c levels in experimentally induced diabetic rats compared to the control group. 18,35 In addition to its anti-hyperglycemic effect, NEEM significantly improved endothelial function in T2DM subjects, compared to the placebo group. No such findings were available in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…13 Many in vitro and in vivo studies have reported hypoglycemic activity of neem extracts, made with different solvents. [15][16][17][18][19][20] Azadirachtin, 21 Nimbidiol 22 and Gedunin and Azadiradione 23 also showed anti-hyperglycemic activity, but toxicity is of concern with these bioactives. Aqueous neem leaf and twig extract used in this study does not contain these bioactives, and showed good antihyperglycemic activity in our pre-clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Chloroform extracts activities were studied in vitro and in vivo in streptozocin-induced diabetic rats (200–300 mg/kg) produced an attenuation of non-enzimatic glycation, inhibiting advanced glycation end product (AGE) formation, and alleviated oxidative stress, increasing the levels of antioxidant enzymes, glucose-6-phosphatase, hepatic glycogen content and insulin plasma levels, and decreasing glucokinase and lipid peroxidation [ 42 , 43 ]. The main mechanism of action of azadirachtins (e.g., azadirachtolide, azadiradione, gedunin and meliacinolin) is the inhibition of α-amylase and α-glucosidase [ 44 , 45 , 46 ].…”
Section: Medicinal Plants Used For the Management Of Diabetesmentioning
confidence: 99%
“…In light of this, catalpol isolated from Rehmannia glutinosa restrains AGE-mediated inflammation by inhibiting ROS production and NADPHoxidase activity and this is considered to prevent AGE-mediated problems in DM [40]. An extract from A. indica also inhibits AGE formation in addition to oxidative stress and it is thought to have a protective effect in diabetic kidney disease [41]. Similarly, a Piper auritum leaf extract has been reported to have concomitant antioxidant as well as AGE inhibitory activities [42].…”
Section: Inhibition Of Advanced Glycation End-product (Age) Formationmentioning
confidence: 99%